PEMBUATAN STRUKTUR ORGANISASI PENGURUS KAMPUNG MANDIRI JAYA SEBAGAI UPAYA MENINGKATKAN TATA KELOLA PEMERINTAHAN DESA - Rulan L Manduapessy; Helensia Limbong Bulaan; Karniati Sanda Pare; Nur Najmiati; Yobelina Tanlain (Adiba Aisha Amira, 2025)
The establishment of the organizational structure of the Kampung Mandiri Jaya Management is a strategic effort to enhance village governance that is participatory, transparent, and accountable. This study aims to examine how a well-planned organizational structure, tailored to local needs, can strengthen institutional capacity and improve the effectiveness of public services. Using a qualitative descriptive approach, the research outlines the formulation process of the organizational structure, the roles of each management member, and its impact on village governance dynamics. The findings reveal that a clear and functional organizational structure fosters better coordination among village apparatus, increases community participation in development, and reinforces accountability in decision-making. Therefore, the formation of the Kampung Mandiri Jaya Management structure serves as a promising model for replication in other contexts of village governance improvement.